2005
DOI: 10.1530/rep.1.0680
|View full text |Cite
|
Sign up to set email alerts
|

Increased disruption of sperm plasma membrane at sperm immobilization promotes dissociation of perinuclear theca from sperm chromatin after intracytoplasmic sperm injection in pigs

Abstract: The effects of sperm-immobilization methods on decondensation of sperm chromatin and retention of subacrosomal sperm perinuclear theca (SAR-PT) after intracytoplasmic sperm injection (ICSI) were examined in pigs. Sperm membrane damage caused by different immobilization methods by rubbing with a micropipette without piezo pulses (R), or with a low (L) or high (H) intensity of piezo pulses while rubbing, was assessed by the time required for staining of sperm heads with eosin Y solution. The average time for sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…4). Interestingly, despite the presence of PLCz in both the head and the tail, injection of whole sperm induced normal fertilization in only 40% of the oocytes (Table 1) and similar results have been published by others (Katayama et al 2005). In contrast, following IVF, nearly 100% of sperm-penetrated oocytes display activation events resulting in PN formation (Kikuchi et al 1999).…”
Section: Discussionsupporting
confidence: 86%
“…4). Interestingly, despite the presence of PLCz in both the head and the tail, injection of whole sperm induced normal fertilization in only 40% of the oocytes (Table 1) and similar results have been published by others (Katayama et al 2005). In contrast, following IVF, nearly 100% of sperm-penetrated oocytes display activation events resulting in PN formation (Kikuchi et al 1999).…”
Section: Discussionsupporting
confidence: 86%
“…Kasai et al (14) reported that oocyte activation, assessed by the completion of meiosis, occurred earlier when spermatozoa were freed from the plasma membrane before ICSI. Increased fertilization rates after ICSI using plasma membrane-removed porcine spermatozoa were reported (15,16). Here, we report that removal of both the plasma membrane and acrosome from mouse spermatozoa before ICSI not only accelerates the onset of oocyte activation but also results in improved embryonic development.…”
mentioning
confidence: 79%
“…taurine and hypotaurine; Petters and Wells 1993)). Also, the benefits induced by CYS reported by Katayama et al (2007) may have been conditioned by combining CYS with the use of piezo pulses for sperm-immobilization to disrupt the sperm plasma membrane, which it is known to improve the fertilization rates and the decondensation of the sperm chromatin after ICSI (Katayama et al 2005). It should be highlighted that in our study the CYS supplement was tested alone, without any other sperm membrane disruptor than the sperm mid-piece rubbing step during ICSI (GarciaMengual et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, and contrarily to what happens after IVF, MPN formation of porcine oocytes in vitro matured with CYS is not improved after ICSI. The persistence of an intact sperm acrosome, plasma membrane and perinuclear theca (Katayama et al 2002a(Katayama et al , 2005, which are normally removed during sperm penetration in IVF and natural fertilization (Yanagimachi 1994), may be some of the factors causing an incorrect MPN formation in ICSI.…”
Section: Introductionmentioning
confidence: 99%